Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1002/app.10574
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of conductive network quality in carbon black‐filled polymer blends

Abstract: Heat treatment of polymer-based composites is critical for the enhancement of both stability and long-term service life, especially when the materials function under an inconstant temperature environment. The present article discusses the effect of heat-treatment conditions on the electrically conductive properties of carbon black (CB)-filled low-density polyethylene (LDPE) and ethylene-vinyl acetate copolymer (EVA) composites, which are candidates for positive temperature coefficient (PTC) materials. It was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…The composites undergoing heating–cooling cycles usually show poor reproducibility of resistivity due to redistribution of particles in the matrix as a result of repeated melting and crystallization 8, 9. Improvement of the reproducibility of resistivity might be achieved through postheat treatment of the composites 4, 10, 11…”
Section: Introductionmentioning
confidence: 99%
“…The composites undergoing heating–cooling cycles usually show poor reproducibility of resistivity due to redistribution of particles in the matrix as a result of repeated melting and crystallization 8, 9. Improvement of the reproducibility of resistivity might be achieved through postheat treatment of the composites 4, 10, 11…”
Section: Introductionmentioning
confidence: 99%
“…The PTC effect strongly depends on the time related thermal history, 19,20 so that thermal aging is becoming a common method to eliminate the thermal history and to stabilize the conduction behavior. 21,22 Tao et al 23 and Park et al 24 found that annealing at temperatures below and above T m has different influences on the redistribution of filler aggregates in the matrix and also on the PTC/NTC behavior of CPCs. Their observations were confirmed by Song and Zheng,20 and were explained with respect to the breakdown and reformation of the percolation network at lower temperatures, as well as the agglomeration of carbon black (CB) aggregates and formation of percolation network in the melts.…”
Section: Introductionmentioning
confidence: 98%
“…4,5 As most of these mechanisms are actually involved with kinetic processes, CPCs often exhibit time-dependent resistance changes at constant temperatures, stresses, or strains. [19][20][21][22][23][24][25][26][27][28][29][30] Many CPCs exhibit a drastic increase in electric resistivity over a temperature range around the melting point (T m ) of the semicrystalline matrix as is termed as positive temperature coefficient (PTC) effect of resistivity, which is usually followed by a rapid resistivity decrease named negative temperature coefficient (NTC) effect. The PTC effect strongly depends on the time related thermal history, 19,20 so that thermal aging is becoming a common method to eliminate the thermal history and to stabilize the conduction behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous methods can be used to influence the selective distribution of CB particles within the continuous phase, and the introduction of a polar component is generally regarded as one of the most convenient and effective methods []. For example, Foulger [] decreased the percolation threshold of the CB‐filled co‐continuous poly(ethylene‐ co ‐vinyl acetate) (EVA)/HDPE composites to ∼4 wt% by selectively localizing CB particles within the EVA phase.…”
Section: Introductionmentioning
confidence: 99%